2019
DOI: 10.3776/tpre.2019.v9n1p23-43
|View full text |Cite
|
Sign up to set email alerts
|

Discourses of the Rural Rust Belt:

Abstract: This article addresses the ways in which elementary teachers in the rural rust belt both reproduce and contest dominant discourses of schooling, rurality, and poverty in their particular local context. Situated within a 4-year postcritical ethnographic study, this analysis of teacher discourse took part during an embedded, 4-month-long teacher study group. Within this context, the authors examine how the group’s discourse on poverty claimed that inequity was the fault of those experiencing it, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Educators also observed that the lack of a university and limited economic opportunities and established low skill labour-market jobs of parents, limited young peoples' aspirations' regarding their education and training trajectories. This finding may also reflect the unconscious bias that teachers have been found to label low-income families in rural settings (Panos and Seelig's 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Educators also observed that the lack of a university and limited economic opportunities and established low skill labour-market jobs of parents, limited young peoples' aspirations' regarding their education and training trajectories. This finding may also reflect the unconscious bias that teachers have been found to label low-income families in rural settings (Panos and Seelig's 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Courtade et al (2017) found the use of online courses, virtual coaching, and online professional learning communities allowed rural special educators to not feel professional isolation and offered more opportunities for collaboration as they accessed a 3-year professional development program. Training for in- and pre-service teachers should include opportunities for educators to reflect on their own experiences related to rurality to better understand their own locale biases (Panos & Seelig, 2019). A list of online training opportunities and resources can be found in Table 2.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…For example, the US Census Bureau denotes that “‘rural’ encompasses all population, housing, and territory not included within an urban area” (United States Census Bureau, 2018, p. 1). Defined thusly, the term is inherently urban normative and forwards predominant sociological depictions of rural communities as regressive in contradistinction to urban progressiveness (Azano and Biddle, 2019; Panos and Seelig, 2019). Moreover, defining rural as “not urban” implicates homogeneity across culturally and geographically distinctive locales.…”
Section: Rethinking Rural Definitionsmentioning
confidence: 99%